دور جودة الخدمات المصرفية في الحد من مشكلة نقص السيولة في الاقتصاد الليبي (Comprehensive Journal of Science, 2025)
This study examines the role of banking service quality in mitigating liquidity shortages in Libyan commercial banks from the perspective of bank customers who are faculty members and employees at the Higher Institute of Science and Technology in Al-Abyar. The study adopts a descriptive–analytical approach and employs a questionnaire as the main data collection instrument based on the SERVQUAL model with its five dimensions (reliability, responsiveness, assurance and trust, tangibles, and empathy), while liquidity shortage is assessed through indicators including ease of access to cash, cash availability, congestion, and overall customer satisfaction. The study sample consisted of 55 respondents, and the data were analyzed using SPSS.     The findings reveal that the overall level of banking service quality was relatively high, with the assurance and trust dimension ranking highest, whereas the empathy dimension recorded the lowest level. The results also indicate the persistence of liquidity shortages, particularly in terms of congestion, delays in banking operations, and difficulty in accessing cash. Furthermore, the study confirms the existence of a strong statistically significant relationship between banking service quality and the reduction of liquidity shortages, highlighting that improving service quality can play an effective role in alleviating this problem and enhancing the operational efficiency of the banking sector.